Input/Output Devices and Interaction Techniques (2004) - Hinckley, Ken; Jacob, Robert J. K.; Ware, Colin (Chapman and Hall/CRC, 2004)
The computing literature often draws a sharp distinction between input and output; computer scientists are used to regarding a screen as a passive output device and a mouse as a pure input device. However, nearly all examples of human-computer interaction require both input and output to do anything useful. For example, what good would a mouse be without the corresponding feedback embodied by the cursor on the screen, as well as the sound and feel of the buttons when they are clicked? The distinction between output devices and input devices becomes even more blurred in the real world. A sheet of paper can be used to both record ideas (input) and display them (output). Clay reacts to the sculptor’s fingers yet also provides feedback through the curvature and texture of its surface. Indeed, the complete and seamless integration of input and output is becoming a common research theme in advanced computer interfaces such as ubiquitous computing (Weiser, 1991) and tangible interaction (Ishii & Ullmer, 1997). Input and output bridge the chasm between a computer’s inner world of bits, and the real world perceptible to the human senses. Input to computers consists of sensed information about the physical environment. Familiar examples include the mouse, which senses movement across a surface, and the keyboard, which detects a contact closure when the user presses a key. However, any sensed information about physical properties of people, places, or things can serve as input to computer systems. Output from computers can comprise any emission or modification to the physical environment, such as a display (including the cathode ray tube (CRT), flat-panel displays, or even light emitting diodes), speakers, or tactile and force feedback devices (sometimes referred to as haptic displays). An interaction technique is the fusion of input and output, consisting of all hardware and software elements, that provides a way for the user to accomplish a low-level task. For example, in the traditional graphical user interface, users can scroll through a document by clicking or dragging the mouse (input) within a scroll bar displayed on the screen (output). Input and output bridge the chasm between a computer’s inner world of bits, and the real world perceptible to the human senses. Input to computers consists of sensed information about the physical environment. Familiar examples include the mouse, which senses movement across a surface, and the keyboard, which detects a contact closure when the user presses a key. However, any sensed information about physical properties of people, places, or things can serve as input to computer systems. Output from computers can comprise any emission or modification to the physical environment, such as a display (including the cathode ray tube (CRT), flat-panel displays, or even light emitting diodes), speakers, or tactile and force feedback devices (sometimes referred to as haptic displays). An interaction technique is the fusion of input and output, consisting of all hardware and software elements, that provides a way for the user to accomplish a low-level task. For example, in the traditional graphical user interface, users can scroll through a document by clicking or dragging the mouse (input) within a scroll bar displayed on the screen (output).